STUDY OF JAMBI COAL DUST CONCENTRATION 53-44 ?m EFFECT ON EXPLOSION PPRESSURE USING SIWEK 20-L CHAMBER - Herlambang Pamungkas Sa, Satria
Coal dust which is dispersed in an enclosed area (e.g. underground coal mines or coal handling facilities) becomes a concern because of its combustible properties. Components to cause fire are oxygen, fuels, and heat source, but to cause an explosion, dispersion and confinement are needed. This research is aiming at analyzing the effect of concentration and dust fineness that may cause an explosion and generate explosion pressure, by using Siwek 20-L Chamber. Based on the research, the Pmax (maximum explosion pressure) value generated by Jambi coal dust explosion is 12.25 bar and the (dP/dt)max (maximum rate of pressure rise) is 465.81 bar/s, the Jambi coal dust is then concluded to cause St 1 explosion which is a weak explosion. In coal dust size range of 53 – 44 ?m, the MEC value is 200 g/m3, but MEC near the PR equal to 2 (a minimum criterion that the dust is explosible) is 125 g/m3. Compared to coal dust size of 74 – 53 ?m (Azwar, 2019), it needs a concentration of 150 g/m3 to cause an explosion. While coal dust size of 74 – 53 ?m explosion pressure falls sharp after 1000 g/m3, coal dust size of 53 – 44 ?m explosion pressure falls sharp after 1400 g/m3¬. The research shows that if the dispersed dust concentration is increased, the explosion pressure will increase. Besides, the finer is the coal dust size, the explosion pressure will also increase. But, with the increase of coal dust size and in thicker concentration (more than 1000 or 1400 g/m3), the explosion pressure falls sharp easily.